Capitalization of In‐Process Research and Development under SFAS 141R and Information Asymmetry - Chung, Hyeesoo (Sally) H.; Hillegeist, Stephen A.; Park, You‐Il (Chris); Wynn, Jinyoung P. (Contemporary Accounting Research, 2019)
ABSTRACT This study examines the effect of capitalizing acquired in‐process research and development (IPR&D) on information asymmetry under Statement of Financial Accounting Standards No. 141 (R) (SFAS 141R). SFAS 141R requires acquirers to fully recognize IPR&D at fair value as an indefinite‐lived intangible asset until completion or discontinuation of the project. Prior research suggests IPR&D capitalization will result in an improvement in the information environment. In contrast, we find no evidence that capitalizing IPR&D improved the information environment for IPR&D acquirers. Instead, most of our results suggest no significant change in information asymmetry for IPR&D acquirers during the post‐SFAS 141R period, relative to the concurrent changes for non‐IPR&D acquirers. In cases in which the results suggest a statistically significant increase, the economic magnitudes are relatively small. In addition, we find no evidence that IPR&D acquirers engaged in increased classification shifting between IPR&D and goodwill during the post‐SFAS 141R period, as critics of capitalization had feared.